Phase change behavior of latent heat storage media based on calcium chloride hexahydrate composites containing strontium chloride hexahydrate and oxidation expandable graphite. (5th June 2016) - Li, Xiang; Zhou, Yuan; Nian, Hongen; Ren, Xiufeng; Dong, Ouyang; Hai, Chunxi; Shen, Yue; Zeng, Jinbo
Highlights: The addition of oxidation expandable graphite reduced the supercooling of PCM. Oxidation expandable graphite improved the heat transfer of PCM. Thermal cycling stability of PCM due to special structure of oxidation expandable graphite and viscosity of SDBS. Abstract: Calcium chloride hexahydrate (CaCl2 ·6H2 O) composites PCMs containing strontium chloride hexahydrate (SrCl2 ·6H2 O) and oxidation expandable graphite (EGO) were prepared and phase change behavior of CaCl2 ·6H2 O/EGO/SrCl2 ·6H2 O composite PCMs, including supercooling degree, phase change temperature, latent heat, density, thermal conductivity and thermal stability were systematically studied. Results demonstrate that thermal conductivity, heat transfer and the latent capacities of the CaCl2 ·6H2 O/SrCl2 ·6H2 O/EGO composite PCMs are significantly enhanced, supercooling of CaCl2 ·6H2 O/SrCl2 ·6H2 O/EGO composite PCMs are suppressed, mainly ascribe to that the EGO are homogenously dispersed in PCMs due to the existence of oxygen-containing functional groups in EGO, meanwhile, the well-dispersed EGO serving as nuclei to promote the heterogeneous nucleation and crystallization process of CaCl2 ·6H2 O. Moreover, a fifty-run-cycling test verifies that the CaCl2 ·6H2 O/SrCl2 ·6H2 O/EGO composites PCMs contained with 3 wt% SrCl2 ·6H2 O, and 1.0 wt% EGO possesses enhanced thermal behavior with no phase segregation observed; the latent heat was calculated to be 172.26 J/g.